THE ROLE OF STREAMING, ONLINE REVIEWS, RATINGS IN INCREASING CUSTOMER ENGAGEMENT WITH TRUST AS A MODERATOR VARIABLE - Vidyastuti, Heppy; Suryana, Popo (Faculty of Economic and Business, University of Pasundan, 2025)
This research is a quantitative study. The population in this study were market place users in West Java. SmartPLS version 4 used to process and analyse data collection result and its results are: 1 The Customer Enggagement affected significantly by Customer trust, 2 The Customer trust affected significantly by live streaming variable, 3 Customer Enggagement affected significantly by The Live Streaming, 4 Online Review variable no effect on Customer Trust , 5 Customer trust variable affected significantly rating, 6.Customer Enggagement affected significantly by rating variable 7. The effect of Live Streaming to the customer enggagement mediated by the customer trust meet the requirements in this study. 8. The effect of Online Review to the customer enggagement mediated by the Customer trust does meet the requirements in this study. 9. The effect rating to customer enggagement mediated by the customer trust meet the requirements in this study